In vitro and in situ study on characterization and mechanism of the intestinal absorption of 2,3,5,4′-tetrahydroxy-stilbene-2-O-β-D-glucoside - Cheng Wang; Yimeng Zhou; Xiaohong Gong; Li Zheng; Yunxia Li (BMC Pharmacology and Toxicology, 2020)
Abstract Background 2,3,5,4′-tetrahydroxystilbence-2-O-β-D-glucoside (TSG) is a polyhydroxyphenolic compound, which exhibited a broad spectrum of pharmacological activities, such as anti-inflammatory, anti-depression, anti-oxidation and anti-atherosclerosis. However, the compound had poor bioavailability and the underlying absorption mechanisms had not been studied. Therefore, the purpose of this study was to investigate the intestinal absorption mechanism of TSG. Methods This study used Caco-2 cell monolayer model and single-pass intestinal perfusion model to explore the gastrointestinal absorption mechanisms of TSG. The effects of basic parameters such as drug concentration, time and pH on the intestinal absorption of TSG were analyzed by high performance liquid chromatography. The absorption susceptibility of TSG to three inhibitors, P-gp inhibitors verapamil hydrochloride and quinidine, and MRP2 inhibitor probenecid were also assessed. Results TSG was poorly absorbed in the intestines and the absorption of TSG in stomach is much higher than that in intestine. Both in vitro and in situ experiments showed that the absorption of TSG was saturated with increasing concentration and it was better absorbed in a weakly acidic environment pH 6.4. Moreover, TSG interacts with P-gp and MRP2, and TSG was not only the substrate of the P-gp and MRP2, but also affected the expression of P-gp and MRP2. Conclusions It was concluded that the gastrointestinal absorption the most unique active ingredient and considered as the mechanisms of TSG involved processes passive transport and the participation of efflux transporters.